A different lens: Changing perspectives using Photo-Elicitation Interviews - Torre, Daniela; Murphy, Joseph (Education Policy Analysis Archives, 2015)
The purpose of this systematic literature review is to document how scholars in various fields have used Photo-Elicitation Interview (PEI), explain the benefits and obstacles to using this method, and explain how and why education researchers should use PEI. The key features of PEI are that a researcher or participant takes pictures about a research topic that are then used to elicit dialogue during an interview. The results of our review suggest that education scholars and school practitioners can use PEI methods to better understand school communities and the children, parents, and school staff who inhabit them. Utilizing this technique, the research community will be better positioned to speak on behalf of school stakeholders when contributing to policy discussions and when seeking solutions to improving schools.